Standard symbols for welding, brazing and nondestructive examination (American Welding Society ; Reproduced by World Engineering Xchange (WEX) with the permission of AWS under royalty agreement, 2007)
"This standard establishes a method for specifying certain welding, brazing, and nondestructive examination information by means of symbols. Detailed information and examples are provided for the construction and interpretation of these symbols. This system provides a means of specifying welding or brazing operations as well as nondestructive examination, including the examination method, frequency, and extent."